Reducing vulnerability to forced labor and trafficking of short-term, low-skilled women migrant workers in the South Asia to Middle East corridor - ElDidi, Hagar; van Biljon, Chloé; Alvi, Muzna; Ringler, Claudia; Ratna, Nazmun; Abdulrahim, Sawsan; Kilby, Patrick; Wu, Joyce; ul Arefin Choudhury, Zahid (2021)
Hagar ElDidi, Chloé van Biljon, Muzna Alvi, Claudia Ringler, Nazmun Ratna, Sawsan Abdulrahim, Patrick Kilby, Joyce Wu and Zahid ul Arefin Choudhury